2016
DOI: 10.1038/srep29933
|View full text |Cite
|
Sign up to set email alerts
|

The myocardial regenerative potential of three-dimensional engineered cardiac tissues composed of multiple human iPS cell-derived cardiovascular cell lineages

Abstract: Human induced pluripotent stem cells (hiPSCs) are a robust source for cardiac regenerative therapy due to their potential to support autologous and allogeneic transplant paradigms. The in vitro generation of three-dimensional myocardial tissue constructs using biomaterials as an implantable hiPSC-derived myocardium provides a path to realize sustainable myocardial regeneration. We generated engineered cardiac tissues (ECTs) from three cellular compositions of cardiomyocytes (CMs), endothelial cells (ECs), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 41 publications
6
127
0
Order By: Relevance
“…We induced multiple CV cell lineages from hiPSCs to generate LF-ECTs using the lineage distribution shown to generate an optimal linear hiPSC-derived ECTs8. We employed two distinct CV cell differentiation protocols to generate either predominantly cardiac troponin-T (cTnT) + CMs and vascular endothelial (VE)-cadherin (CD144) + endothelial cells (ECs) or to generate predominantly platelet-derived growth factor receptor beta (PDGFRβ; CD140b) + vascular mural cells (MCs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We induced multiple CV cell lineages from hiPSCs to generate LF-ECTs using the lineage distribution shown to generate an optimal linear hiPSC-derived ECTs8. We employed two distinct CV cell differentiation protocols to generate either predominantly cardiac troponin-T (cTnT) + CMs and vascular endothelial (VE)-cadherin (CD144) + endothelial cells (ECs) or to generate predominantly platelet-derived growth factor receptor beta (PDGFRβ; CD140b) + vascular mural cells (MCs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even with a broad range of evidence-based therapies, the five-year survival rate of heart failure remains as low as approximately 50%1. Numerous preclinical studies and clinical trials have suggested that application of stem and/or progenitor cell populations to an injured heart may hold a potential to ameliorate left ventricular dysfunction caused by ischemic and dilated cardiomyopathy accompanying heart failure2345678. Among various cell types, human induced pluripotent stem cells (hiPSCs) are considered highly promising cell sources for cardiac regenerative cell therapy, because the fundamental etiology of heart failure is the result of massive loss or dysfunction of myocardial cells9, and various cardiovascular (CV) cell lineages can be scalably produced from iPSCs101112.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another perspective is the supplementation of other cell lineages consisting native heart tissue such as vascular cells (vascular endothelial cells or vascular mural cells), or stromal cell lineages (e.g., cardiac fibroblasts) besides cardiomyocytes. Cell sheet experiments or 3-D engineered cardiac tissue experiments have shown that the co-existence of vascular cells with cardiomyocytes within the structure promotes reinforced secretion of humoral factors working on tissue repair, cellular alignment or sarcomeric maturation (7,19 (20). These results indicate the importance of co-existence of various cardiac cell lineages among the 3-D construct, and that the addition of electrical stimulation potentially further enhances tissue maturation.…”
mentioning
confidence: 79%
“…Cardiac cells differentiated from hiPSCs mostly used for recent studies in this research field are juvenile and immature, and have only acquired characteristics of terminally differentiated cell lineages for 1-2 months. These cells are equivalent to cells at the fetal stage at the first trimester of pregnancy (7)(8)(9)(10). It has been reported that the electrophysiological properties of the vast majority of hiPSC-derived cardiomyocytes lack the I K1 current leading to immature repolarization capacity (16) which encourages researchers to drive cellular maturation, and also maturation as a tissue.…”
mentioning
confidence: 99%